2018
DOI: 10.1177/1756284818787408
|View full text |Cite
|
Sign up to set email alerts
|

Management of occult obscure gastrointestinal bleeding patients based on long-term outcomes

Abstract: Background:There is no consensus regarding the management of occult obscure gastrointestinal bleeding (OGIB) patients without a confirmed bleeding source. This study aimed to consider the management of occult OGIB patients based on their long-term outcomes.Methods:We retrospectively enrolled 357 consecutive occult OGIB patients (203 men; mean age: 59.7 years) who underwent capsule endoscopy (CE) at Hiroshima University Hospital, Japan and were followed up for more than 12 months (mean follow-up period; 50.2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Endoscopic capsule lesions ("E") are stratified regarding their risk of gastrointestinal bleeding according to Saurin classification: P2 lesions have a high bleeding potential, P1 lesions a mild bleeding risk, and P0 lesions a very low risk. As expected, taking into account findings described by Kunihara et al [25], we found the highest rebleeding rate for patients with P2 lesions, followed by those with P1 lesions [17]. The different SBCE findings are stated in Table 1: nodules, lymphangiectasias, red spots, erosions, angioectasiae, ulcers, and tumors.…”
Section: Mgib Is Associated With High Morbidity Indexessupporting
confidence: 83%
“…Endoscopic capsule lesions ("E") are stratified regarding their risk of gastrointestinal bleeding according to Saurin classification: P2 lesions have a high bleeding potential, P1 lesions a mild bleeding risk, and P0 lesions a very low risk. As expected, taking into account findings described by Kunihara et al [25], we found the highest rebleeding rate for patients with P2 lesions, followed by those with P1 lesions [17]. The different SBCE findings are stated in Table 1: nodules, lymphangiectasias, red spots, erosions, angioectasiae, ulcers, and tumors.…”
Section: Mgib Is Associated With High Morbidity Indexessupporting
confidence: 83%
“…The certainty of evidence was very low due to high risk of bias (selection bias due to inclusion of symptomatic patients and patients referred to specialty centers for CE). [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123] Additionally, in a recent study that followed 93 patients with IDA for more than 5 years, no small bowel malignancies were identified. 124 However, the comparative efficacy of CE in IDA remains undefined.…”
Section: After Negative Bidirectional Endoscopy In Patients With Iromentioning
confidence: 99%
“…An investigation of the causes of bleeding in patients with occult obscure gastrointestinal bleeding at our institution indicated that 83% of these patients had treatment-adapted lesions. Furthermore, 49% of patients had a history of LC; however, the bleeding sources were vascular lesions such as angioectasia and varices [37].…”
Section: Discussionmentioning
confidence: 99%